PERBANDINGAN PENGGUNAAN SAPAAN PRONOMINA PERSONA DALAM KOMIK RUROUNI KENSHIN DENGANBEELZEBUB - Aryasuari, Istri (Humanis, 2015)
This research entitles “The Comparison ofPronouns Addressing Usage in Rurouni Kenshin with Beelzebub Comics”. This research aims at knowing of pronouns addressing terms found in both comics. The theory used in this research is T-V Brown-Gilman Theory in 1960. The methods used are referential comparative method. The result of this research shows that there are some pronouns addressing terms found in both comics which have same intimate form, respect form, intimate function, respect function, solidarity meaning, and authority meaning, for example pronouns addressing.Pronouns addressing terms found in both comics are ore, washi, oretachi, orera, kimi, omae, temee, kisama, koitsu, aitsu, watashi, watashitachi, anata and anta. There are differences and similarities of intimate form, respectform, intimate function, respect function, solidarity meaning, and authority meaning of pronouns addressing terms found in both comics. Also, there are some pronouns addressing terms which have the intimate form, respect form, intimate function, respect function, solidarity meaning, and authority meaning but can only be found in one comic. Pronouns which only found in Rurouni Kenshin comic are bokura, washira, koitsura, soitsura, ware, anatatachiandantara. Pronouns which only found in Beelzebub comic are boku, kimitachi, temeera, aitsura, watakushi, watashira, antatachiandminasan.
Keywords: forms, functions, meanings, pronouns addressing terms